Sequential imaging of intraneural sciatic nerve endometriosis provides insight into symptoms of cyclical sciatica - Capek, Stepan; Amrami, Kimberly K; Howe, Benjamin M; Collins, Mark S; Sandroni, Paola; Cheville, John C; Spinner, Robert J (Acta neurochirurgica, 2016)
Endometriosis of the nerve often remains an elusive diagnosis. We report the first case of intraneural lumbosacral plexus endometriosis with sequential imaging at different phases of the menstrual cycle: during the luteal phase and menstruation. Compared to the first examination, the examination performed during the patient's period revealed the lumbosacral plexus larger and hyperintense on T2-weighted imaging. The intraneural endometriosis cyst was also larger and showed recent hemorrhage. Additionally, this case represents another example of perineural spread of endometriosis from the uterus to the lumbosacral plexus along the autonomic nerves and then distally to the sciatic nerve and proximally to the spinal nerves.
Keywords: Female; lidé středního věku; endometrióza; menstruace; Uterus; Luteal Phase; Uterine Hemorrhage; Menstruation; Recurrence; magnetická rezonanční tomografie; Sciatic Nerve; Sciatica; Humans; Lumbosacral Plexus; Endometriosis; ischialgie; lidé; uterus; menstruační cyklus; plexus lumbosacralis; Middle Aged; Magnetic Resonance Imaging; ženské pohlaví; recidiva; luteální fáze; nervus ischiadicus; děložní krvácení; Menstrual Cycle